Experimental and Analytical Studies on Low-Cost Glass-Fiber-Reinforced-Polymer-Composite-Strengthened Reinforced Concrete Beams: A Comparison with Carbon/Sisal Fiber-Reinforced Polymers - Kittipoom Rodsin; Ali Ejaz; Qudeer Hussain; Rattapoohm Parichatprecha (My University, 2023)
This study presents an experimental framework with seventeen beams to investigate the impact of loading type, configuration, and through-bolt anchorage on LC-GFRP (Low-Cost Glass-Fiber-Reinforced Polymer) confinement performance. Beams underwent three-point and four-point bending, with LC-GFRP applied in various ways, including U-shaped, side-bonded, and fully wrapped, with and without anchors. The performance of LC-GFRP was compared to CFRP (Carbon-Fiber-Reinforced Polymer) and sisal wraps. LC-GFRP in side-bonded and U-shaped configurations without anchors under three-point bending showed no shear failure, while those under four-point bending without anchors experienced shear failure. With anchors, U-shaped configurations successfully prevented shear failure. The side-bonded, U-shaped, and U-shaped configurations along the full span with anchors demonstrated peak capacity enhancements of 72.11%, 43.66%, and 68.39% higher improvements than the corresponding configurations without anchors, respectively. Wrapping all sides of the beam with LC-GFRP or CFRP prevented shear failure without additional anchors, with complete wrapping being the most efficient method. When anchors were used, significant capacity enhancements were observed. Existing shear strength prediction models were evaluated, highlighting the need for more tailored expressions for LC-GFRP confinement, especially for non-U-shaped configurations.
Keywords: Structural Behavior of Reinforced Concrete